Discover Honolulu, Waikiki & O'ahu experience the best of O'ahu - McLachlan, Craig 1962- (Footscray, Victoria, Australia Lonely Planet Publications Pty Limited, 2015)
This full-color guide reveals the island's beaches, sights and off-the-beaten track adventures so you can discover the real Oahu. Realize your dream vacation with insider insights, honest reviews and simple planning tools. Highlights reveal the must-see attractions and unbeatable experiences. Itineraries make planning your ultimate vacation simple. Sustainable travel tips and resources. Easy-to-use maps make getting around the island a breeze.
Includes index.
Includes bibliographical references, filmography (page 27), discography (page 27), and indexes.
Keywords: Honolulu (Hawaii) -- Guidebooks; Oahu (Hawaii) -- Guidebooks; Waikiki (Honolulu, Hawaii) -- Guidebooks